Fire Safety Assessment at Block G2 FKMP, Universiti Tun Hussein Onn Malaysia - Mohd Samsuri, Mohammad Haziq; Ismail, Shafawi (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Fire safety awareness and preparedness among Malaysian university students remain a key concern, as many studies have found gaps in training, infrastructure, and behavioral readiness despite current safety measures and awareness efforts. This study reveals numerous significant factors influencing fire safety preparation among university inhabitants, including limited participation in fire drills, lack of fire extinguisher training, insufficient awareness of emergency procedures, and inadequate visibility of safety signage and equipment. The emphasis of this study is specifically on tenants of Block G2 under the Faculty of Mechanical and Manufacturing Engineering (FKMP) at University Tun Hussein Onn Malaysia (UTHM), Parit Raja. The purpose is to examine the level of fire safety knowledge, preparedness, and the effectiveness of present fire safety measures. Data was obtained from 102 respondents through structured questionnaires and processed using SPSS software version 27. The findings of the ANOVA analysis revealed no significant differences (at p = 0.05) in fire safety awareness across demographic variables such as age, year of study, gender, department, and role. However, Pearson correlation analysis indicated high statistical connections (r > 0.5, n = 102, p < 0.05) between knowledge of fire alarms, frequency of fire drills, and evacuation confidence, demonstrating that these factors strongly affect readiness. It is intended that the findings of this research would assist FKMP in strengthening fire safety culture and emergency response preparation among students and staff. Based on the results, proposed treatments include enhancing fire safety training programs, increasing the frequency of fire drills, improving the visibility of safety signage, and adding digital alert systems to strengthen overall campus safety management.